EFEKTIVTAS PEMANFAATAN ALOKASI DANA DESA DI DESA UJUNG BATU TIMUR KECAMATAN UJUNG BATU KABPATEN ROKAN HULU TAHUN 2015 - Firmansyah "; Zaili Rusli MD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Village Allocation Fund is a part of the central and regional equalization funds devoted to the village in implementing government services and community empowerment. But in reality the effectiveness of the implementation and management is still not maximized. The existance of human resources is inadequate, the construction of facilities and infrastructure are still yet to be realized. The problem in this research is how the effectiveness Ujung Batu Timur village government in achieving its goal in utilizing the Village Fund Allocation and the factors that influence the effectiveness of.This study aims to determine the effectiveness of utilization of the Village Fund Allocation In the village of Ujung Batu Timur District of Rokan Hulu. The concept of the theory that researchers use is organizational effectiveness by using Gibson’s theory by looking at the goals to be achieved Clarity, Clarity goal attainment strategy, process analysis and formulation of policy steady, careful planning, preparation of appropriate programs, availability of infrastructure and surveillance systems and control didactic.The method used is qualitative research with descriptive data assessment. In collecting the data, the researcher used interview techniquess, observation and documentation speciefied by snowball sampling tecnique. The results showed that the utilization of the Village Fung Allocation In the village of Ujung Batu Timur District Of Rokan Hulu has not been effective because there are many village fund allocation unrealized. Also foud are also government programs that have not been implemented village. The factors that influence the effectineness of the utilizationof the Village fund Allocation In The village of Ujung Batu Timur district of Rokan Hulu is a lack of human resources, poor coordination and lack of community participation in the implementation of.Keyword: Effectiveness, Utilization, Village Allocation Fund (ADD)